Hak Hukum dan Waris Anak Bayi Tabung Dari Pernikahan Tidak Tercatat - Habibulloh Habibulloh; Ishaq Ishaq; Muhammad Faisol (Fakultas Hukum Universitas Islam Jember, 2026)
Even though it is considered valid under Islamic law, unregistered marriages are not recognized under positive law because they are not officially recorded. This raises crucial legal issues regarding the status of children born through IVF, which are only considered valid when the sperm and egg come from a legally married couple, as stipulated in Article 58 of Law Number 17 of 2023 concerning Health. This poses a risk of loss of legal and inheritance rights for children born from IVF in unregistered marriages, especially if there is no marriage certificate. This study analyzes two themes, namely IVF and unregistered marriages in Islamic law and positive law, as well as the legal and inheritance rights implications for children born from IVF in unregistered marriages. This study uses library research by examining secondary data sourced from books, journals, legislation, and previous studies. The Miles & Huberman method is used to analyze the data. The results show that: (1) children born from IVF in unregistered marriages are not legally valid under positive law, and their rights are limited unless the marriage is validated; (2) if the child is born from donor sperm without the husband's consent, the child is considered illegitimate. However, once the marriage is validated and the donor's consent is obtained, the child's rights are fully protected by the state.